2018
DOI: 10.1155/2018/8023840
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating Iron Overload in Intestinal Tissue of Adult Male Rats: Quercetin vs Deferoxamine

Abstract: Objective The aim of our study is to compare the role of the new natural alternative (Quercetin) with the current iron-chelation therapy (Deferoxamine (DFO)) in the effect of iron overload on small intestinal tissues and to investigate the possible underlying molecular mechanisms of such toxicity. Methods Forty-two adult male albino rats were divided into six groups: control groups, DFO, Quercetin, iron overload, iron overload+DFO, and iron overload+Quercetin groups. Animals received daily intraperitoneal inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 59 publications
2
9
0
Order By: Relevance
“…Several studies used genetic or induced iron-overloaded animal models 12,[22][23][24][25][26] , but none showed bleeding tendency or coagulation abnormality, raising the question of what is different between the dietary model of this study and other iron-overloaded models. Of these studies, some studies using rat models have reported elevated transferrin saturation compared to that in each control; about 76% in TfR2 mutant iron-overloaded Sprague-Dawley rat 23 , 92.5% in intraperitoneally administered dextran iron-induced iron-overloaded albino rats 24 , and 95.9% in orally administered citrate iron-induced iron-overloaded Wistar rats 25 . This study showed that dietary citrate iron-induced iron-overloaded F344 rats had the same degree of transferrin saturation (95.6%).…”
Section: Discussionmentioning
confidence: 96%
“…Several studies used genetic or induced iron-overloaded animal models 12,[22][23][24][25][26] , but none showed bleeding tendency or coagulation abnormality, raising the question of what is different between the dietary model of this study and other iron-overloaded models. Of these studies, some studies using rat models have reported elevated transferrin saturation compared to that in each control; about 76% in TfR2 mutant iron-overloaded Sprague-Dawley rat 23 , 92.5% in intraperitoneally administered dextran iron-induced iron-overloaded albino rats 24 , and 95.9% in orally administered citrate iron-induced iron-overloaded Wistar rats 25 . This study showed that dietary citrate iron-induced iron-overloaded F344 rats had the same degree of transferrin saturation (95.6%).…”
Section: Discussionmentioning
confidence: 96%
“…The reduction in liver iron caused by rutin may have been insufficient to affect the expression levels of some genes, such as Tfr1, whose expression levels are usually inversely correlated with cellular iron stores. Under iron overload conditions in wild type animals, Hamp expression levels would be expected to Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20210720/915403/bsr-2021-0720.pdf by guest on 28 June 2021 decrease upon iron chelation (38) to promote absorption and redistribution of iron stores. However, the absence of a change in Hamp in our study is likely due to dysregulated hepcidin regulation resulting from the lack of Tfr2 in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…After activation with HistoVT One, the immunocomplex was visualized by the avidin-biotin-peroxide method using the Vecstatin Elite ABC Rabbit IgG kit, according to the manufacturer's instructions. Sections were counter-stained with haematoxylin (16,18).…”
Section: Immunohistochemical Analysismentioning
confidence: 99%